Comparative assessment of urinary oxidative indices in breast and colorectal cancer patients - Chandramathi, S.; Suresh, K.; Anita, Z.B.; Kuppusamy, U.R. (2009)
This study aimed to use non-invasive methods to assess and compare the levels of oxidative indices and non-enzymatic antioxidants in breast and colorectal cancer (CRC) patients. Various studies have reported on lipid peroxidation, hydrogen peroxide (H(2)O(2)) and ferric-reducing antioxidant power (FRAP) levels in the serum of cancer patients but this is the first report that highlights the significance of urinary-advanced oxidative protein product (AOPP) in cancer patients. The levels of advanced oxidative protein product (AOPP), hydrogen peroxide (H(2)O(2)), malondialdehyde (MDA) which is a marker for lipid peroxidation and ferric-reducing antioxidant power (FRAP) were measured in urine samples of breast (n = 101) and colorectal cancer (n = 49) patients attending the Oncology Clinic, University Malaya Medical Centre, Kuala Lumpur and were compared with 95 age-matched healthy individuals. AOPP, H(2)O(2) and MDA levels in the urine were significantly higher in the CRC patients compared to the control subjects and breast cancer patients. In breast cancer patients, only AOPP level was elevated. FRAP level did not differ between breast and colorectal cancer patients but the levels were significantly lower compared to control subjects. Urinary oxidative indices such as AOPP, H(2)O(2), and MDA as well as FRAP could serve as useful non-invasive oxidative stress markers in colorectal cancer but only AOPP serves as a useful urinary oxidative biomarker in breast cancer.